Reduction on Proinflammatory Cytokines after Application of Transcutaneous Electrical Nerve Stimulation (TENS) in Patients with a Breast Cancer: A Nonrandomized, Open, and Single-Arm Study Protocol with Paired Analysis - Tábata Cristina do Carmo Almeida; Simone Meneghette Zatta; Laércio da Silva Paiva; Luís Eduardo Werneck de Carvalho; Jean Schoueri; Luiz Carlos de Abreu; Fernando Luiz Affonso Fonseca; Fernando Adami (Mediators of Inflammation)
Background. Transcutaneous electrical nerve stimulation (TENS) has been used as analgesic therapy in many diseases. It is already known that studies that have observed the relationship between pain and cytokines have found that patients who report less severe pain have less production of proinflammatory cytokines. However, one another accepted mechanism is that decreasing proinflammatory cytokines results in decreased pain intensity. Analyzing the literature, the authors describe that, in addition to the analgesic effect, TENS has shown systemic effects, and clinically, the reduction of proinflammatory cytokines could be a protective factor against inflammation. To test the inflammatory effect of TENS, we researched the literature for clinical conditions that suggest that proinflammatory cytokines are one of the main mediators of the disease process. Chronic inflammation is one of the risk factors mentioned for the development of a new cancer; at the same time, it is indicated as an indicator of the worst prognosis. Studies also suggest that the worst prognosis of breast cancer, one of the types with the highest incidence in the world, may be related to increased inflammatory activity. Considering that inflammation is increased in breast cancer and that TENS can reduce proinflammatory cytokines even without blocking the pain pathway, our hypothesis is that the anti-inflammatory effect of TENS can bring benefits to these patients. The aim of this study will be to evaluate the effect of TENS on blood reduction of proinflammatory cytokines in breast cancer patients. Methods. This study will evaluate at least 59 patients, over 18 years of age, diagnosed with breast cancer, but who have not yet started any treatment. All patients will be submitted to TENS intervention (Ibramed, Model Neurodyn III, parameters: VIF—turn on, frequency—2-247 Hz, pulse size—50-500 μs, and intensity (mA)—maximum tolerated by the patient), and the data will be analyzed in the pre- and postintervention of each patient. The application has a total duration of 30 minutes, and 8 ml of blood will be collected before and after the intervention. Proinflammatory (IL-1, IL-2, IL-6, IL-7, and TNF-α) and anti-inflammatory (IL-4, IL-10, IL-13, and FTCβ) cytokines will be analyzed. As a primary endpoint, we will analyze the reduction in blood concentration of proinflammatory cytokines, and as secondary endpoints, we will analyze the size of the effect according to each type of proinflammatory cytokine, describe the effect size of the reduction according to the breast cancer immunohistochemistry, and analyze the effect of TENS on anti-inflammatory cytokines. This study is approved by the Research Ethics Committee (Centro Universitário FMABC, Brazil) and registered in the Brazilian Clinical Trials (Search text: RBR-10jbwh47).